Drugs in development for treatment of patients with cancer-related anorexia and cachexia syndrome - Mantovani G; Madeddu C; Maccio A (Dove Medical Press, 2013)
Giovanni Mantovani, Clelia Madeddu, Antonio Macciò Department of Medical Oncology, University of Cagliari, Cagliari, Italy Abstract: Cancer-related anorexia and cachexia syndrome (CACS) is a complex multifactorial condition, with loss of lean body mass, chronic inflammation, severe metabolic derangements, reduced food intake, reduced physical activity, and poor quality of life as key symptoms. Cachexia recognizes different phases or stages, moving from precachexia through overt cachexia to advanced or refractory cachexia. The purpose of this review is to describe currently effective approaches for the treatment of cachexia, moving forward to drugs and treatments already shown to be effective but needing further clinical trials to confirm their efficacy. We then introduce novel promising investigational drugs and approaches which, based on a strong rationale from the most recent data on the molecular targets/pathways driving the pathophysiology of cachexia, need to be tested either in currently ongoing or appropriate future clinical trials to confirm their clinical potential. Although different drugs and treatments have been tested, we can speculate that a single therapy may not be completely successful. Indeed, considering the complex clinical picture and the multifactorial pathogenesis of CACS, we believe that its clinical management requires a multidisciplinary and multitargeted approach. In our opinion, appropriate treatment for cachexia should target the following conditions: inflammatory status, oxidative stress, nutritional disorders, muscle catabolism, immunosuppression, quality of life, and above all, fatigue. A comprehensive list of the most interesting and effective multitargeted treatments is reported and discussed, with the aim of suggesting the most promising with regard to clinical outcome. A critical issue is that of testing therapies at the earliest stages of cachexia, possibly at the precachexia stage, with the aim of preventing or delaying the development of overt cachexia and thereby obtaining the best possible clinical outcome for patients. Keywords: proinflammatory cytokines, nutritional status, metabolic derangements, quality of life, cachexia staging, multimodal therapy